Service Delivery Indicators : Tanzania - World Bank (Washington, DC, 2014)
The indicators, which were piloted in Tanzania, provide a set of metrics to benchmark the performance of schools and health clinics in Africa. The indicators can be used to track progress within and across countries over time, and aim to enhance active monitoring of service delivery to increase public accountability and good governance. The service delivery indicators project takes as its starting point the literature on how to boost education and health outcomes in developing countries. This literature shows robust evidence that the type of individuals attracted to specific tasks at different levels of the service delivery hierarchy, as well as the set of incentives they face to actually exert effort, are positively and significantly related to education and health outcomes. To evaluate the feasibility of the indicators, pilot surveys in primary education and health care were implemented in Tanzania in 2010. The results from the pilot studies demonstrate that the indicators methodology is capable of providing the necessary information to construct harmonized indicators on the quality of service delivery, as experienced by the citizen, using a single set of instruments at a single point of collection. This paper is structured as follows: section one gives introduction. Section two outlines the analytical underpinnings of the indicators and how they are categorized. Section three presents the methodology of the pilot surveys in Tanzania. The results from the pilot are presented and analyzed in section four. Section five presents results on education outcomes, as evidenced by student test scores. Section six discusses the advantages and disadvantages of collapsing the indicators into one score or index, and provides a method for doing so in case such an index is deemed appropriate. Section seven discusses lessons learned, trade-offs, and options for scaling up the project.